Perception of the person who lives with HIV / AIDS and their families in relation to the care in the hospitalization: Considering the index of anxiety and depression - Quintanilha , Analice Cristhian Flavio; Nascimento, Valdir Aragão; Souza, Albert Schiaveto de (International Journal for Innovation Education and Research, 2021)
The human immunodeficiency virus (HIV) was discovered in the 1980s, it affects the immune system and when not treated with appropriate medications it can lead the person to develop acquired immunodeficiency syndrome (AIDS). The antiretroviral therapy (ART) that makes HIV undetectable was discovered in 1990. However, despite the free ART in Brazil, there is still a challenge regarding the adherence of people (100%) living with HIV/AIDS (PLWHA), because the abandonment of the medication or the non-regular use reduces future treatment options which cause illness and death. The objective of this research was to understand the perception of the person living with HIV/AIDS and their family members, regarding the care offered in the infectious and parasitic diseases unit. In addition, the anxiety and depression rate that affects them during the hospitalization period will be considered. This study was carried out in the Infectious and Parasitic Inpatient Sector DIP Infirmary (Enf/DIP), which is part of the Infectious and Parasitic Diseases Unit (UNIDIP) of the Hospital Maria Aparecida Pedrossiam (HUMAP), in the municipality of Campo Grande - MS. The prospective collection of primary data was obtained through questionnaires that were replaced by words and expressions in the title and in the content. Changes were made and elaborated with the objective of improving the understanding of the sentences, which became a semantic evaluation of content by a committee of evaluators. Thus, before the final application of the questionnaire to the participants, all the steps cited constituted the methodological strategies for capturing data.